PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN HALMAHERA UTARA - KABIAY, OSNAVITA; POSUMAH, JOHNNY HANNY; KOLONDAM, HELLY FEBRINA (Sam Ratulangi University, 2017)
Summary : This study aims to determine and analyze the influence of supervision on the discipline of employeesof the Regional Secretariat of North Halmahera Regency. Research Methods that the authors use in this studyis a quantitative research method. Data and information collected through questionnaire technique andcompleted with interview technique, data source / respondent of research is all secretariat officer of northHalmahera regency area as much 80 people. Analytical techniques used by hypothesis testing are frequencytables, product moment correlation and simple linear regression. Based on the description of the data it turns outmost of the respondents are giving an assessment of the surveillance are in the variables category of